Fix your team : the tools you need to rebuild relationships, address conflict and stop destructive behaviours - Bryant-Smith, Rose; Beard, Grevis (John Wiley & Sons Australia, Ltd, 2018)
Transform team dynamics with practical, real-world tools for sustainable change Fix Your Team is the manager's essential and practical guide to diagnosis and intervention. Packed with expert insight acquired over decades of experience in workplace relations and conflict resolution, this book systematically addresses problems with team dynamics and provides a blueprint for moving forward. Authors Rose Bryant-Smith and Grevis Beard bring a unique combination of legal nous, conflict management expertise, emotional intelligence and business experience to provide a wealth of valuable insights, with robust tools designed for easy implementation. This book offers diagnostic guidance to help you analyse existing issues with confidence, and a clear framework for removing the dysfunction. It includes practical scenarios we can all relate to, and actionable guidance on building buy-in, executing the strategy and looking after yourself through tough transformations. By tackling problems early and providing employees with the opportunity to improve their working relationships, managers, human resources and other internal advisors demonstrate their commitment to productivity, genuine care for employees and dedication to a healthy and ethical working environment. People working in dysfunctional teams will understand better what is going on, and understand what options exist for improvement.-Diagnose team problems and learn what tools are available to help -Determine the best use of resources and choose an implementable fix -Develop a business case for intervention, and get support from the top -Build morale, productivity and collaboration within the team -Upskill employees to ensure sustainable improvements -Build accountability in everyone for a positive workplace culture In today's competitive environment, managers need to bring out the best in everyone. Team dysfunction affects productivity at all levels, and it's contagious - managers must stop the problem before it spreads, to prevent larger and more pervasive issues down the road. Remediating team issues reduces legal and safety risks, but it goes deeper than that. Solving problems before they become public or impact other areas of the business improves the team's respect for managers and leadership, reducing unnecessary turnover and resignations of good staff. Fix Your Team is a groundbreaking handbook for management looking to improve team dynamics, with practical solutions for productivity-killing, unethical and distracting issues. It gives all managers and internal advisors the confidence, strategies and solutions they need to repair tricky, toxic and troubled teams to create a great workplace.